Design of automobile instrumentation - Aslfallah, Akhtar (2008)
The thesis was the final work contributing to a Master‟s degree in Industrial Design at Luleå University of Technology in collaboration with Volvo. The goal was to produce a concept proposal suitable for drivers using appropriate theories for the design. It was performed as a part of the project OPTIVe (OPTimized system integration for safe Interaction in Vehicles). Volvo Car Corporations vision is to develop automobiles for modern families: their cars are built on the principles of safety, quality and environmental care. Which leads to the basis of this project where the focus of creating a concept proposal according to attractiveness, safety, ergonomics and Scandinavian design. The project would result in a number of design concepts for the instrument panel in the automobile. In the end, an evaluation of the concepts was to be performed in the semantic environmental description. Evaluations of the six concepts in the semantic environmental description were studied by ten subjects. The subjects were presented with different instrument panel pictures and answered with formulary questionnaire and the results were statistically analyses using Microsoft Excel. The result of the concept evaluation phase and analysis was Concept A as the most innovative and pleasing solution. Concept E had the highest total score, while the concept A displayed the most pleasantness, unity, potency and social status. Concept A has Easy to understand functions, is a product for many car models and has harmonious curves and shapes, with function. Validerat; 20101217 (root)